Development of graphical user interface for open source VLSI digital synthesis tool Qflow - Roy, K. Sripath; Abhiram, K.; Sumanth, M. Arun; Jaishankar, Jaishree; Abhishek, P.; Prabhat, B. Nikhil; Teja, L. Gnana (International Journal of Engineering and Technology, 2018)
There are many tools that are used for simulation in the domain of VLSI technology but none of them are easily accessible. There is a need for Free and open source tools in this stream so as to make them accessible to everyone. There are efficient tools that already exist in open source in VLSI stream but are not used widely because of their command line user interface. Hence, creating a user friendly interface will help many developers and users to work easily. This paper deals with the idea to solve the above issue by creating a Graphical User Interface for the open source VLSI tool called QFlow. Qflow is a tool used in synthesizing a VLSI circuit from the Verilog source code. There are multiple tools integrated with this tool to assure the simulation process. It is a combination of many dependencies that are used for synthesis, placement, layout viewing and routing in a fabrication process. All the independent tools used for the Verilog code simulation are integrated onto a single platform. Qt is used for creating the cross-stage application.
Keywords: VLSI; Qflow; Qt; Verilog